Violence and insecurity at the Kwamashu hostel in KwaZulu-Natal - Xulu-Gama, Nomkhosi (Acta criminologica, 2017)
This article is based on an ethnographic study of the KwaMashu Community Residential Units (CRUs) (hostel), which took place between 2009 and 2011 and looks at one aspect of daily life in the CRUs, i.e. that of interpersonal and group violence. Group violence was generally political in nature and the parties involved were the Inkatha Freedom Party, the African National Congress and the National Freedom Party. These political parties have a long history of violent antagonism. The second type of violence that will be discussed is interpersonal violence. This generally took the form of gender violence, mostly directed at women. All of these forms of violence have made the CRU under review a very unsafe place to live. Focus group discussions, observations and interviews were used to explore the daily lives of the CRU dwellers. The article argues that while histories of antagonism between the various political parties and patriarchy contribute in very direct ways to contemporary violence, the actual built-up environment of the CRU is also a contributing factor.